2019
DOI: 10.1128/jvi.00168-19
|View full text |Cite
|
Sign up to set email alerts
|

Simian-Human Immunodeficiency Virus SHIV.CH505-Infected Infant and Adult Rhesus Macaques Exhibit Similar Env-Specific Antibody Kinetics, despite Distinct T-Follicular Helper and Germinal Center B Cell Landscapes

Abstract: Global elimination of pediatric human immunodeficiency virus (HIV) infections will require the development of novel immune-based approaches, and understanding infant immunity to HIV is critical to guide the rational design of these intervention strategies. Despite their immunological immaturity, chronically HIV-infected children develop broadly neutralizing antibodies (bnAbs) more frequently and earlier than adults do. However, the ontogeny of humoral responses during acute HIV infection is poorly defined in i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 71 publications
(90 reference statements)
5
41
0
Order By: Relevance
“…We took the opportunity to compare the viral replication kinetics and reservoir in infant RMs to that of adult RMs infected with the same SHIV strain from a separate study, and thus a cohort of convenience (26). Six adult RMs, were intravenously infected with SHIV.CH505.375H.dCT (see methods) and started on triple ART regimen of TDF, FTC and DTG at 12 w.p.i.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We took the opportunity to compare the viral replication kinetics and reservoir in infant RMs to that of adult RMs infected with the same SHIV strain from a separate study, and thus a cohort of convenience (26). Six adult RMs, were intravenously infected with SHIV.CH505.375H.dCT (see methods) and started on triple ART regimen of TDF, FTC and DTG at 12 w.p.i.…”
Section: Resultsmentioning
confidence: 99%
“…However, we previously demonstrated that vaccination of infants can induce robust HIV Env-specific IgG responses (41). Moreover, we recently reported that infant monkeys are capable of mounting durable anti-HIV humoral immune responses during acute SHIV infection, despite their maturing immune landscape (26). In this study, we observed comparable humoral immune responses between the two age groups during ART and post-ATI (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations